Relevansi Penggunaan Teknologi dalam Penanggulangan Kejahatan Cybercrime di Indonesia - Murshad Kashif; Naufal Ghibran (Universitas Sains dan Teknologi Komputer, 2023)
Surakarta City's Economic Growth in 2020 is -1.74%. Based on the growth rate of GRDP at constant prices, it shows that the Surakarta City economy is dominated by 3 sectors, namely Construction at 25.59%, Wholesale and Retail Trade, Car and Motorcycle Repair at 22.34% and Information and Communication at 18.54%. The trade sector in Surakarta City is a sector that is superior to Surakarta City because of its geographical location as a transit city through which Jakarta-Surabaya traffic passes so that it influences trade development. Products traded are closely related to the industrial and agricultural sectors. Export-oriented trade is carried out by companies with large production scales. Products traded include textile products and handicrafts. In addition, there are two sub-sectors supporting trade in Surakarta City, namely the hotel and restaurant sub-sectors which are also growing. The trade and services sector as well as tourism are the leading sectors in all sub-districts in Surakarta City, so that from a regional spatial planning perspective it becomes part of the Spatial Structure planning of Surakarta City.